Internal and External Performance Evaluation Analysis (Sakip) at the Investment and One-Door Integrated Services Service (Dpmptsp) of East Java Province - Nesya Kamila Andanika (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study analyzes the internal and external performance evaluation systems through the Government Agency Performance Accountability System (SAKIP) at the East Java Province Investment and One-Stop Integrated Services Agency (DPMPTSP). The research focuses on the internal performance evaluation mechanism, the external evaluation process, and factors influencing the quality of organizational performance. The study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results show that internal evaluation is carried out through monitoring the implementation of the Work Plan and Action Plan uploaded to the SIAKIP system, but still faces technical and administrative obstacles, especially in utilizing the evaluation results for planning for the following year. External evaluations are conducted by six evaluators who produce SAKIP rankings, with the achievement of the East Java DPMPTSP score reaching 81.51 in 2024 with a ranking of 41st. Factors influencing performance quality include the alignment of planning documents, leadership involvement, internalization of work culture, consistency of monitoring and evaluation, and the suitability of performance reporting